CERITA PENDEK ANAK DALAM MAJALAH BOBO TAHUN 1980â€AN SEBAGAI BACAAN PENDIDIKAN KARAKTER - Saptawuryandari, Nurweni (ATAVISME, 2014)
This article aims to describe the national character values in children short stories in Bobo magazine. As a children magazine, Bobo always publishes children short stories in every issue. Data of this research is twenty-four children short stories in Bobo magazine published by Gramedia in 1983?s. The data was collected through librarian study. The method used is the descriptive-qualitative one which explains the writings based on the content. The result shows that children short stories in Bobo magazine contain national character values. Those values contain moral teaching. The short stories were written by adults. They describe lives, responsibility, religion, self-service, discipline, hard working and love of the environment. This article aims to describe the national character values in children short stories in Bobo magazine. As a children magazine, Bobo always publishes children short stories in every issue. Data of this research is twenty-four children short stories in Bobo magazine published by Gramedia in 1983?s. The data was collected through librarian study. The method used is the descriptive-qualitative one which explains the writings based on the content. The result shows that children short stories in Bobo magazine contain national character values. Those values contain moral teaching. The short stories were written by adults. They describe lives, responsibility, religion, self-service, discipline, hard working and love of environment. Key Words: children story; adult; character values Abstrak: Tulisan ini bertujuan mendeskripsikan nilai-nilai karakter bangsa yang terdapat dalam cerita pendek anak-anak di majalah Bobo. Sebagai majalah anak-anak, Bobo dalam setiap terbitannya selalu memuat cerita pendek anak-anak yang mengandung unsur dulce et utile. Data penelitian ini adalah dua puluh empat cerita pendek anak-anak dalam majalah Bobo terbitan Gramedia tahun 1983. Pengumpulan data dilakukan dengan studi pustaka. Metode yang digunakan adalah deskriptif kualitatif yang memaparkan tulisan berdasarkan isi karya sastra. Hasil penelitian menunjukkan bahwa cerita pendek anak-anak yang ada di majalah Bobo mengandung nilai-nilai karakter bangsa yang berkaitan dengan pendidikan moral dan budi pekerti. Cerita yang ditulis orang dewasa itu menggambarkan masalah kehidupan dan mengandung nilai karakter jujur, tanggung jawab, religius, mandiri, disiplin, kerja keras, dan cinta lingkungan.